Culicoides Oxystoma a Potential Vector for Transmission of Bluetongue Virus 16 in Southern India - Ranjan, Koushlesh; Prasad, Minakshi; Brar , Basanti; Prasad , Gaya (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Bluetongue (BT) is a Culicoides vector borne disease of domestic and wild ruminants. It is caused by bluetongue virus (BTV). BT is infectious but non-contagious disease. The head–thorax region of Culicoides Oxystoma vector trapped on animal farm in TN was triturated and inoculated in BHK 21 cell culture. After few blind passages it showed cytopathic effect (CPE) in cell culture. After appearance of 75% cytopathic effect in BHK 21 cell culture, viral nucleic acid was extracted. The RNA-PAGE analysis showed BTV specific characteristics migration pattern of 3:3:3:1. Viral nucleic acid was allowed for cDNA synthesis followed by NS1 and VP2 gene based RT-PCR. The NS1 gene RT-PCR, CPE and specific migration pattern in RNA-PAGE confirmed the sample as BTV. The VP2 gene based serotype specific RT-PCR identified the isolate as BTV serotype 16. The study suggested that Culicoides oxystoma could be a potential vector for transmission of BTV in southern India.
Keywords: Bluetongue virus 16; Serotype; VP2 gene; RT-PCR; Vector